Efeitos do gel intravaginal de policarbofila na qualidade dos espermatozoides - Ana Carolina Xavier Goulart (2022)
The lack of adequate vaginal lubrication is twice as prevalent in infertile women undergoing treatment to become pregnant when compared to the general population. In an attempt to control dryness, it is common to use lubricants and vaginal moisturizers. One of the alternatives is the use of non-hormonal polycarbophil intravaginal gel. However, the possible effects of this gel on sperm quality are not well established. The present study aims to evaluate the possible effects of intravaginal polycarbophil gel on sperm quality in vitro. Aliquots of semen samples (n = 166) were incubated at 34°C for 24 hours in a 1:1 ratio with polycarbophil gel prediluted to 20% in a culture medium (final dilution of the gel = 10%), or only with the culture medium, also in a 1:1 ratio (control group). Seminal analyzes were performed at different times (0, 15, 30 min and 24h) to determine concentration, motility, and vitality of the sperm in the sample after contact with the gel. Sperm counts decreased from a median of 50 x 10⁶ /mL in fresh samples to 38 x 10⁶ /mL after incubation with culture medium and to 36 x 10⁶ /mL after incubation with polycarbophil gel (p<0,0001). The proportion of progressive sperm motility decreased from a median of 52% in fresh samples to 11% after 24h of incubation with culture medium and 0% after 24h of incubation with gel (p<0,0001). Sperm motility reduced immediately after contact of the seminal sample with gel and throughout the experiment, in contrast to incubation with culture medium, which affected sperm motility only after 24h. Over time, there was a decrease in sperm count in both experimental conditions, being more evident in samples treated with polycarbophil gel (p = 0.001). The vitality analyzed after 24h of incubation differed between treatments, with a median of 62.5% with exposure to the culture medium and 47% with the polycarbophil gel (p= 0,020). We conclude that the use of polycarbophil gel can be harmful to sperm quality, and therefore it should not be recommended to couples undergoing infertility treatment.